2005
DOI: 10.1111/j.1751-0813.2005.tb11657.x
|View full text |Cite
|
Sign up to set email alerts
|

Third metacarpal bone laterality asymmetry and midshaft dimensions in Thoroughbred racehorses

Abstract: In this sample of racehorses longer MC3 bones were likely to have been exposed to a greater dorsopalmar bending moment at the mid shaft that was reflected in a thicker dorsal cortex. The lack of a relationship between midshaft thickness and bone length within individual horses suggests that direct mechanical effects of conformation and environment were less important than the individual's level of skill (or the degree of laterality in their movements) developed before their exposure to fast exercise. It is lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
1
10
1
2
Order By: Relevance
“…The studies confirmed the phenomenon of asymmetry regarding the femoral bones in this species [18] and the equine third metacarpal [19]. Importantly recent study found that the majority of proximal phalanx fractures in horses occur in the right leg [20].…”
Section: Introductionsupporting
confidence: 75%
“…The studies confirmed the phenomenon of asymmetry regarding the femoral bones in this species [18] and the equine third metacarpal [19]. Importantly recent study found that the majority of proximal phalanx fractures in horses occur in the right leg [20].…”
Section: Introductionsupporting
confidence: 75%
“…According to Watson et al. () and Davies and Watson (), the right Mc3 is longer than the left Mc3 in Thoroughbred racehorses in Victoria and South Australia, whereas Weller et al. () did not find any significant differences between the lengths of the right and left Mc3 bones of 108 National Hunt racehorses.…”
Section: Introductionmentioning
confidence: 98%
“…Some authors have taken their measurements directly from bone specimens using traditional tools such as callipers and rulers (Davis, ; Guintard and Lallemand, ; Nacambo et al., ), while others measured the lengths directly on the bones using standard field‐measurement procedures and an osteometric board (Mcfadden and Bracht, , ). Although the changes in the focus‐film and object‐film distances can lead to the magnification of the objects on the film (Curry et al., ; Walter and Davies, ), several studies have involved the use of radiographs to measure some human and animal bones (Aydinlioglu et al., ; Livshits et al., ; Watson et al., ; Davies and Watson, ; Anthenill et al., ; Dogan et al., ). Many authors photographed horses with skin markers to measure some equine joint angles and bone dimensions (Crevier‐Denoix et al., ; Anderson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Fato é que a associação de diminuição da intensidade do exercício com crioterapia, fototerapia, eletroestimulação e fonoterapia permitiu que os animais permanecessem em exercício durante o período de tratamento e retornassem ao esquema de treinamento para corridas em 30 dias. É importante frisar que a velocidade e a duração do exercício (NUNAMAKER et al, 1990;BOSTON & NUNAMAKER, 2000), bem como a habilidade individual do animal em suportar exercícios de alta intensidade (DAVIES & WATSON, 2005), estão diretamente correlacionadas com o aparecimento da enfermidade e com a porcentagem de recidivas. A impossibilidade de evitar a ocorrência de uma variável não prevista no protocolo, o tipo de trabalho imposto aos animais após o tratamento, interferiu no índice de recidivas da enfermidade.…”
Section: Discussionunclassified